A randomised, open-label, parallel group phase 2 study of antisense oligonucleotide therapy in acromegaly. Issue 2 (August 2018) - Trainer, Peter J; Newell-Price, John D C; Ayuk, John; Aylwin, Simon J B; Rees, Aled; Drake, William; Chanson, Philippe; Brue, Thierry; Webb, Susan M; Fajardo, Carmen; Aller, Javier; McCormack, Ann I; et al.
Abstract : Objective: ATL1103 is a second-generation antisense oligomer targeting the human growth hormone (GH) receptor. This phase 2 randomised, open-label, parallel-group study assessed the potential of ATL1103 as a treatment for acromegaly. Design: Twenty-six patients with active acromegaly (IGF-I >130% upper limit of normal) were randomised to subcutaneous ATL1103 200 mg either once or twice weekly for 13 weeks and monitored for a further 8-week washout period. Methods: The primary efficacy measures were change in IGF-I at week 14, compared to baseline and between cohorts. For secondary endpoints (IGFBP3, acid labile subunit (ALS), GH, growth hormone-binding protein (GHBP)), comparison was between baseline and week 14. Safety was assessed by reported adverse events. Results and conclusions: Baseline median IGF-I was 447 and 649 ng/mL in the once- and twice-weekly groups respectively. Compared to baseline, at week 14, twice-weekly ATL1103 resulted in a median fall in IGF-I of 27.8% ( P  = 0.0002). Between cohort comparison at week 14 demonstrated the median fall in IGF-I to be 25.8% ( P  = 0.0012) greater with twice-weekly dosing. In the twice-weekly cohort, IGF-I was still declining at week 14, and remained lower at week 21 than at baseline by a median of 18.7% ( P  = 0.0005). Compared to baseline, by week 14, IGFBP3 and ALS had declined by a median of 8.9% ( P  = 0.027) and 16.7% ( P  = 0.017) with twice-weekly ATL1103; GH had increased by a median of 46% at week 14 ( P  = 0.001). IGFBP3, ALS and GH did not change with weekly ATL1103. GHBP fell by a median of 23.6% and 48.8% in the once- and twice-weekly cohorts ( P  = 0.027 and P  = 0.005) respectively. ATL1103 was well tolerated, although 84.6% of patients experienced mild-to-moderate injection-site reactions. This study provides proof of concept that ATL1103 is able to significantly lower IGF-I in patients with acromegaly.